PENGARUH PEMBELAJARAN JIGSAW DAN PROBLEM BASED LEARNING TENTANG MITIGASI BENCANA GEMPA BUMI TERHADAP KEMAMPUAN ANALISIS SITUASI PADA SISWA KELAS X IPS SMA NEGERI 1 GEMOLONG SRAGEN - Nindi Pradipta Kustanti; Heribertus Soegiyanto; Peduk Rintayati (GeoEco, 2017)
The objectives of this research are to investigate : (1) the effect of between using Jigsaw learning and Problem Based Learning on the analytical skills of students about the earthquake disaster mitigation; (2) the effect of between students who have a high initial capability with lower initial ability on the analytical skills of students about earthquake disaster mitigation; (3) the effect of the interaction between the learning model and the ability of students to the initial situation analysis capabilities of earthquake disaster mitigation in class X IPS SMA Negeri 1 Gemolong Sragen 2015/2016. This research used a quasi experimental research method with the factorial design of 2x2. It involved two classes, namely: experimental class and control class. The data of research were collected through test of Earthquake Disaster Mitigation and Ability Questionnaire Initial Earthquake. They were analyzed by using the two way analysis of variance (ANAVA). The results of the research are follows: 1) In the main effects of A (Learning Model), the statistical value of probabillitas (sig.) = 0.000 <0.05 then Ho is rejected. This means that there is a very significant effects between the application of the jigsaw and PBL learning model to the students on the analytical skills of class X IPS SMA Negeri 1 Gemolong; 2) On the effect of B (early Capability), the value probabillitas (sig.) = 0.000 <0.05 then Ho is rejected. This means that there is a very significant effects between students with the high early capability and those with the low early capability on the analytical skills of students of class X IPS SMA Negeri 1 Gemolong; 3) In the interaction effect AB (learning model and early abilities of students), probabillitas value (sig.) = 0,032 <0.05 then Ho is rejected. This means that there is a significant interaction between the learning models and the use of prior knowledge of the students analytical skills situation in the IPS class X SMA Negeri 1 Gemolong. Keywords: Ability analysis of the situation, Jigsaw, Problem Based Learning.